Digital and Non-Digital Services Influence on Costumers Satisfaction Through Syariah Bank Transactions - Nst, Indah Tri Adisti; Nasution, Salman (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study seeks to determine the impact of digital services, such as mobile banking, e-commerce, and flexible cashless payments, as well as non-digital services like teller services, customer services, and deposit boxes, on customer satisfaction. Specifically focusing on the university students at Muhammadiyah University of North Sumatera (UMSU), the study employed purposive sampling by selecting FAI students who have used mobile banking and other digital services in Islamic banking. The data analysis was conducted using SPSS through three main steps: instrument test, classical assumption test, and hypothesis test. The findings of this research reveal that both digital and non-digital services have a partial and simultaneous impact on customer satisfaction. In line with these results, Islamic bank digital services were found to be in demand among users. Therefore, banks are encouraged to enhance both digital and non-digital services as a strategic approach to attract more customers and enhance overall service quality.